Insights from the world’s first Mobility-as-a-Service (MaaS) system - Weinreich, Marianne; Riihelä, Atte (Proceedings from the Annual Transport Conference at Aalborg University, 2019)
As the world continues to urbanize — and more people attempt to navigate within and between cities and their peripheries — so too continues the development of more efficient modes of transportation, new niches of transport modes and services, and a more intuitive integration of modes to simplify the trip-making process for users. Perhaps most notably, changes are happening in the field of transportation due to the rapid application of technology. What has been a growing “menu” of discrete mobility options offered mostly by public agencies is now becoming a “spectrum” of mobility options; the differences between individual modes are blurring and mobility services are provided by a more complex mix of public and private operators. The most relevant combinations are now finding their way to the user based on their priorities, making mobility effortless and intuitive. This, ultimately, is the aim of Mobility-as-a-Service (MaaS), and the focus of this report.